2014
DOI: 10.1007/s40273-014-0203-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Disease-Modifying Agents: A Simulation Framework for Alzheimer’s Disease

Abstract: The updated economic model has good predictive power, but validation against longer-term outcomes is still needed. Our analyses also demonstrate the importance of designing a model with sufficient flexibility such that the model allows for assessment of the impact of key sources of uncertainty on the value of DMAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…In this ailment, there is an impairment of the cerebral cortex with complex processes; involving the production of senile plaques, neurofibrillary tangles, synapse loss and neuroinflammation; leading to the progressive cognitive decline and memory loss [ 2 , 3 ]. At the present time, about 50 millions of people worldwide suffer from the disease, which creates a heavy burden on the health care systems of many countries [ 4 , 5 , 6 ]. Therefore, discovery of novel drugs for AD is an urgent task.…”
Section: Introductionmentioning
confidence: 99%
“…In this ailment, there is an impairment of the cerebral cortex with complex processes; involving the production of senile plaques, neurofibrillary tangles, synapse loss and neuroinflammation; leading to the progressive cognitive decline and memory loss [ 2 , 3 ]. At the present time, about 50 millions of people worldwide suffer from the disease, which creates a heavy burden on the health care systems of many countries [ 4 , 5 , 6 ]. Therefore, discovery of novel drugs for AD is an urgent task.…”
Section: Introductionmentioning
confidence: 99%
“…2014 Weibull shape: 1.85 Weibull scale: 4.60 + 0.11 BsAge – 0.0009 BsAge 2 + 0.33 Female + 0.023 BsMMSE Institutionalization Guo et al. 2014 In institutional care by MMSE (%) Mild (25–30) 0.0 Mild-moderate (20–24) 0.0 Moderate (15–19) 3.2 Moderate-severe (10–14) 17.1 Severe (0–9) 39.3 Disease severity MMSE thresholds [18] CDR-SB thresholds [19] ADAS-Cog13 thresholds [20] CN 29–30 0–0.5 0–4 SMC 28–29 0.5–1 4–7 EMCI 26–28 1–2.5 7–12 LMCI 25–26 2.5–4.5 12–15 Mild AD 23–25 4.5–7 15–21 Mild-moderate AD 20–23 7–9.5 21–28 Moderate AD 15–20 9.5–13 28–43 Moderate-severe AD 10–15 13–16 43–56 Severe AD 0–10 16–18 56–85 Utilities Patients [17] 0.99-0.041 DS Caregiver …”
Section: Methodsmentioning
confidence: 99%
“…In the alternative approach, results derived from the Dependence in AD in England study are used to assign a probability of institutionalization to each patient based on disease severity level [17] . The user should take into account the differences in the structure of long-term care systems when picking between different approaches.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, it is likely that mortality will need to be modelled based on patient characteristics and their expected disease progression. Available models have clearly shown that differences in assumptions can have a significant effect on results [43][44][45] and the nuances of modelling mortality alongside AD progression.…”
Section: Uncertain Mortality Effects Of Treatment May Have Large Effementioning
confidence: 99%